Long-term Consequences of Undiagnosed Celiac Seropositivity - Kårhus, Line Lund; Skaaby, Tea; Petersen, Janne; Madsen, Anja Lykke; Thuesen, Betina Heinsbæk; Schwarz, Peter; Rumessen, Jüri J.; Linneberg, Allan (The American journal of gastroenterology, 2020)
Diagnosed celiac disease (CD) is associated with lymphoproliferative malignancy and gastrointestinal cancer, but little is known about the long-term consequences of undiagnosed CD. We aimed to investigate long-term consequences of undiagnosed CD for mortality and incidence of cancer and other chronic diseases. We screened biobank serum samples for immunoglobulin (Ig) A and IgG tissue transglutaminase (TTG) and IgG deamidated gliadin peptide in a study of 8 population-based cohort studies comprising 16,776 participants examined during 1976-2012 and followed with >99% complete follow-up in Danish nationwide registries until December 31, 2017, regarding vital status and incidence of diseases. Undiagnosed CD was defined as antibody positivity (IgA-TTG or IgG-TTG ≥ 7 U/mL and/or IgG deamidated gliadin peptide ≥ 10 U/mL) in individuals without a diagnosis of CD recorded in the National Patient Register. Hazard ratios (HRs) with 95% confidence intervals (CIs) were estimated by Cox regression analyses with age as the underlying time scale. The prevalence of undiagnosed CD was 1.0% with no statistically significant increase over time. Undiagnosed CD was associated with increased risk of cancer overall (HR, 1.57; 95% CI, 1.16-2.11), gastrointestinal cancer (HR, 2.33; 95% CI, 1.35-4.04), cancer of the uterus (HR, 3.95; 95% CI, 1.46-10.69), breast cancer (HR, 1.98; 95% CI, 1.02-3.82), head and neck cancer (HR, 3.12; 95% CI, 1.15-8.43), and cardiovascular disease (HR, 1.37; 95% CI, 1.01-1.85). We found no statistically significant association between undiagnosed CD and mortality (HR, 1.19; 95% CI, 0.87-1.61). Undiagnosed CD was associated with increased risk of cardiovascular disease and cancer suggesting that untreated CD has serious long-term health consequences not only affecting the gastrointestinal tract (see Visual Abstract, Supplementary Digital Content, http://links.lww.com/AJG/B566).